Governance for human development: the role of external partners - Cheema, G. Shabbir; Maguire, Linda (2001)
There is a positive correlation between democratic governance and human development. Democratic governance is governance infused with the principles of, inter alia, equity, participation, rule of law, transparency and accountability. Human development is at its very core the expansion of people's choices and their increased participation in decisions that affect their lives. Therefore democratic governance reinforces human development, and human development reinforces democratic governance. External partners - those actors outside of the national development process - can positively contribute to a country's transition to and consolidation of democratic governance (and, thereby, its human development) in a number of ways. External partners act through democratic governance entry points to deliver strategic services and use indicators to measure their relative progress. Indicators can be valuable tools in informing external partners and recipients of assistance of what works, what does not work and why. - Reproduced
Keywords: Human development; Public administration